SGLT-2i: Nanoparticular-based strategies, solutions, and clinical applications in opposition to low bioavailability - YEŞİLDAĞ, OSMAN (My University, 2023)
Purpose: Although SGLT-2i initially acquired prominence for usage in diabetes, they later emerged as the top medication class in both cardiovascular diseases and disorders. However, they still do not have the proper bioavailability (50–70%); therefore, it has different options such as using either a higher dose amount or dose frequency. Methods: The aim of this review is focusing on current trials of SGLT-2i with less side effects and improved patient compliance, which lead to different options such as using either a higher dose amount or dose frequency. Results: With the acceleration of clinical studies, it would not be surprising to witness the introduction of SGLT-2i nano-based systems as a commercial product in the upcoming years. Conclusion: Research on SGLT-2i-based systems is being conducted to facilitate the development of new drug delivery methods such as microemulsion and self-nanoemulsifying drug delivery system. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; TROPİKAL TIP; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; TROPICAL MEDICINE; BIOCHEMISTRY & MOLECULAR BIOLOGY; Farmasötik bilim; İlaç Keşfi; Pharmaceutical Science; Drug Discovery; Bioavailability; Cardiovascular disease; Diabetes; Nanoapproaches; New drug delivery systems; SGLT-2 inhibitors; Side effects; Cardiovascular disease; Bioavailability; Nanoapproaches; SGLT-2 inhibitors; New drug delivery systems; Diabetes; Side efects